HTML, XHTML, and CSS bible - Schafer, Steven M. (Wiley Pub., 2008)
Covers a gamut of HTML topics, such as: documents, elements, entities, values and units, META tags and headers, links, images, tables, frames, forms, multimedia, and internationalization/localization.